Cztery miecze księcia Jerzego II brzeskiego w drezdeńskiej zbrojowni (Rüstkammer) - Stefano Rinaldi (Quart)
The article focuses on a group of four longswords at the Dresden Armoury, which, according to an early inventory entry, came from the possession of Duke George II of Brzeg (1523–1586). The group is identified as a likely diplomatic gift by the Silesian duke to the elector of Saxony; the political backdrop of such a gift is discussed, and a possible occasion proposed. After a typological and functional analysis of the swords, the article places the objects in the context of the German fencing culture of the Renaissance. An excursus identifies two further gifts from the dukes of Legnica and Brzeg in the Dresden Rüstkammer.